Gait and Stability Analysis of 3-PUU Wheel-legged Mobile Robot - Miao Zhiying; Li Ruiqin; Zhang Qisheng; Liang Jingjing; Meng Hongwei; Liang Shijie (Jixie chuandong)
The wheel-legged robot has the advantages of fast moving velocity of wheeled robot and strong passing obstacle capability of legged robot,and it is the development direction of new type mobile robot. A kind of wheel-legged mobile robot based on 3-PUU parallel mechanism is presented. It has advantages of simple structure,high stiffness and strong carrying capacity. The leg walking gait of 3-PUU wheel-legged mobile robot is analyzed. The wheel and leg switch principle and the steering principle under wheel type mode are explained.The stability of robot moving on the road surface is analyzed according to the calculation of gravity,and the maximum step is determined. The trajectory equation is derived by using three spline interpolation and the variation rules of displacement,velocity and acceleration are obtained by using Matlab software. The simulation results show that the robot can achieve continuous and stable walking. The robot can be used in the rescue tasks such as underground coal mines and other dangerous environments.